Ufora Cosmetics / Robiyatul Adawiyah Mohd Shokri - Mohd Shokri, Robiyatul Adawiyah (2021)
Ufora Cosmetics Sdn Bhd was founded by Madam Supia Saupi in 2017. At that time she was obsessed with cosmetics products and had experimented with all kinds of beauty products. However, she saw flaws in most beauty products, and she wanted to fix them by starting her own cosmetics line. All her hard work and sacrifices paid off when her product line received overwhelmingly positive responses from Ufora’s consumers. Being grateful for what she has achieved, and seeing potential in the future of Ufora Cosmetics, she decided to share this business opportunity to other businesswomen and businessmen who are either still struggling or who are hungry for business growth. Until today Ufora Cosmetics still sustains its brand and will strive to grow stronger along with its stockists and agents.